Pengembangan Media Pembelajaran Menggambar Teknik Untuk Mahasiswa Berbasis Android - Satrio Ajie Minarto; I Wayan Sugita; Ahmad Kholil (Risenologi, 2021)
This  research aims to develop Engineering drawing learning media for students based on Android using Adobe Flash Professional CS6 software. The development method used in this research is Research and Development (R&D) with the ADDIE development model, The stages are: Analysis, Design, Development, Implementation, and Evaluation. The method used in data collection is using a questionnaire. In the material validation trial, the learning media got a percentage score of 80% and was included in the "Valid" category. Furthermore, in the media validation trial, the learning media got a percentage score of 70.67% and was included in the "Valid" category. Then the results of small group trials involving 5 students got a percentage score of 92.53% and were included in the "Very Practical" category. While the results of field trials involving 20 students got a percentage score of 91.40% and were included in the "Very Practical" category. Based on these data, thus the android-based engineering drawing learning media is valid and feasible to be used as a learning media for mechanical engineering education students.